Industrial training report: Jabatan Agama Islam Selangor (JAIS) / Muhammad Najmi Ismady - Ismady, Muhammad Najmi (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Completing an industrial training is compulsory for Diploma in Information Management students at Universiti Teknologi Mara in order to finish their studies. This report highlights the knowledge, skills, and experiences of the student that partakes in his industrial training at the Jabatan Agama Islam Selangor, under the Information Technology Unit that is located in Bangunan Sultan Idris Shah, Shah Alam, Selangor. The duration of the students’ undergoing the industrial training is about 8 weeks from 22nd July 2024 to 13th September 2024. The report has been structured into five chapters, which consist of Introduction, Organisational Information, Industrial Training Activities, Learning Outcomes and Achievements, and Recommendations and Conclusions. This report is presented with the desire to offer the other students the precious insights and experience of a trainee who has completed his industrial training period in information management-related fields.